An ongoing path of element-labeling/tagging strategies toward quantitative bioanalysis using ICP-MS. Issue 2 (7th February 2016) - Liang, Yong; Yang, Limin; Wang, Qiuquan
ABSTRACT: In the past dozen years, inductively coupled plasma–mass spectrometry (ICP-MS) has emerged as a spectacular tool for quantitative bioanalysis with the development of element-labeling/tagging strategies. These strategies are paving the way for ICP-MS-based bioanalysis from endogenous heteroelement labels through chemoselective to biospecific exogenous element tags, accompanied by great improvements in sensitivity and selectivity and thus accuracy as well. In this minireview, we critically describe such a developing process, focusing on the research activities performed in our laboratory and some achievements of enlightening significance. A look into the future of ICP-MS-based bioanalysis is proposed regarding the element-tagging strategy and analysis of microorganisms, novel methodological developments for gene and protein sequencing, and the mechanisms of a certain biological process to further understand the occurrence of disease and developments for relevant drug discovery and design, in addition to analysis of biomarkers for disease diagnosis.